Contemporary Progress in the Applications of Iron-based Magnetic Nanoparticles in Multicomponent Synthesis: A Review - Srivastava, Neelanjana; Verma, Monika; Thakur, Ajay; Bharti, Ruchi; Sharma, Renu (Current Organic Chemistry, 2022)
In recent decades, organic synthetic reactions have advanced towards greener and sustainable reactions through the usage of magnetic nanoparticles (MNPs). These MNPs are used as an alternative to resolve the limitations of conventional materials. Amongst various MNPs, iron-based nanoparticles (NPs) are being profoundly explored. The main objective of this review targets to equip its readers a brief introduction to Iron-based MNPs, their properties, evolution and advantage in multicomponent reactions (MCRs) since 2010. MNPs have sown a great impact on multiple fields viz., biomedicine, environmental remediation projects, and catalysis. These are smaller and have a high surface area that allows them to have copious catalytic sites. MNPs can be recovered and reused in various organic syntheses using an external magnet conveniently. MNPs are a sustainable methodology while encountering environmental and profitable advantages. Studies revealed the degradation of catalytic activity after fewer cycles of utilization which is a good research gap to further study on.
Keywords: multicomponent reactions